1805 Mass. Acts 111-13 - (:unkn) unknown (My University, 1805)
Ch. 81: Authorized the governor to appoint two provers per county who would prove musket and pistol barrels before sale. Proven barrels stamped. Violators fined ten dollars.
Keywords: MANUFACTURE ONLY